Effect of Electroacupuncture on Cell Apoptosis and ERK Signal Pathway in the Hippocampus of Adult Rats with Cerebral Ischemia-Reperfusion. (8th November 2015) - Wu, Chunxiao; Wang, Jiao; Li, Chun; Zhou, Guoping; Xu, Xiuhong; Zhang, Xin; Lan, Xiao
Abstract : Background . EA therapy is a traditional therapeutic approach for alleviation of cerebral I/R-induced brain injury. We investigated the effect of EA on MCAO rat model to examine the mechanism of apoptosis in the rat hippocampus. Methods . 200 male Sprague-Dawley rats were randomly divided into sham, I/R, EA, ERK inhibitor (PD), and ERK inhibitor+EA (PD+EA) groups. Each group was subdivided into 5 groups according to different time points. Locomotor behaviors were evaluated using neurological scales and morphological examination was performed using HE staining. Apoptosis index of neural cells in local infarcted area was measured by TUNEL and p-ERK expression was detected using immunohistochemistry technique and western blot analysis. Results . Neurological deficit scores and neural apoptosis in the EA group were lower than I/R group at the same time points, respectively. At different time points, p-ERK level was increased in the ischemic hippocampal CA1 in the EA group as compared to I/R group; the increased level was increased most at 1 day, 3 days, and 1 week (p < 0.01 ). Conclusion . EA alleviates neurological deficit, reduces apoptosis index, and simultaneously upregulates the expression of p-ERK signal pathway in rats subjected to I/R injury.